Analisis Yuridis Aturan Penerapan Denda Administratif Bagi Masyarakat yang Tidak Menggunakan Masker Pada Saat Beraktivitas dan Berkegiatan di Luar Rumah Berdasarkan Peraturan Bupati Buleleng Nomor 41 Tahun 2020 - Kadek Desy Pramita; I Gede Susila Yuda Putra; Kadek Boby Reza Arya Dana (Universitas Pendidikan Ganesha, 2020)
This research was conducted with the aim of knowing and understanding the juridical analysis of the rules for implementing administrative fines for people who do not use masks while on the move and doing activities outside the home according to Buleleng Regent Regulation Number 41 of 2020 concerning the Application of Discipline and Law Enforcement of Health Protocols as Efforts to Prevent and Control of Corona Virus Disease 2019 in a New Era of Life. This research is a research that uses normative research methods, using a statutory approach. Then analyzed descriptively qualitatively using primary, secondary, and tertiary legal materials to get conclusions that are relevant to the problems at hand. The results show that the application of administrative fines for people who do not use masks while on the move and doing activities outside the home in Buleleng Regent Regulation Number 41 of 2020 is based on Presidential Instruction Number 6 of 2020 and Instruction of the Minister of Home Affairs Number 4 of 2020. As for the amount the fine was adopted from Bali Governor Regulation Number 46 of 2020.